The angiotensin-(1-7)/Mas axis counteracts angiotensin II-dependent and -independent pro-inflammatory signaling in human vascular smooth muscle cells - Laura A Villalobos; Álvaro San Hipólito; Mariella Ramos-González; Elena Cercas; Susana Vallejo; Alejandra Romero; Tania Romacho; Raffaele Carraro; Raffaele Carraro; Carlos F Sánchez-Ferrer; Concepción Peiró (Frontiers Media S.A., 2016)
Background and aims: Targeting inflammation is nowadays considered as a challenging pharmacological strategy to prevent or delay the development of vascular diseases. Angiotensin-(1-7) is a member of the renin-angiotensin system (RAS) that binds Mas receptors and has gained growing attention in the last years as a regulator of vascular homeostasis. Here, we explored the capacity of Ang-(1-7) to counteract human aortic smooth muscle cell (HASMC) inflammation triggered by RAS-dependent and -independent stimuli, such as Ang II or interleukin (IL)-1.Methods and Results: In cultured HASMC, the expression of iNOS and the release of nitric oxide were stimulated by both Ang II and IL-1, as determined by Western blot and indirect immunofluorescence or the Griess method, respectively. iNOS induction was inhibited by Ang-(1-7) in a concentration-dependent manner. This effect was equally blocked by two different Mas receptor antagonists, A779 and D-Pro7-Ang-(1-7), suggesting the participation of a unique Mas receptor subtype. Using pharmacological inhibitors, the induction of iNOS was proven to rely on the consecutive upstream activation of NADPH oxidase and NF-B. Indeed, Ang-(1-7) markedly inhibited the activation of the NADPH oxidase and subsequently of NF-B, as determined by lucigenin-derived chemiluminiscence and electromobility shift assay, respectively.Conclusion: Ang-(1-7) can act as a counter-regulator of the inflammation of vascular smooth muscle cells triggered by Ang II, but also by other stimuli beyond the RAS. Activating or mimicking the Ang-(1-7)/Mas axis may represent a pharmacological opportunity to attenuate the pro-inflammatory environment that promotes and sustains the development of vascular diseases.